“Taste of your Hometown”: Evoking Nostalgia through the Diner Space in Midnight Diner - Gupta, Gunjan; Chattaraj, Dishari (SARE: Southeast Asian Review of English, 2023)
Food, Memory, Space, and Storytelling are intertwined. They are formed and reformed, produced and reproduced, and their nuances shape and are shaped by individual experiences. The paper looks at this curious intersection in a Japanese web series, The Midnight Diner, an adaptation of a Manga by Yaro Abe. A tiny not-so-popular restaurant in one of the back lanes in Tokyo, serves from midnight to 7 am, makes several important connections between food and memory as the customers come with specific food cravings and the Master (the owner-chef of the Diner) is happy to customize. The space of the diner acquires different meanings as do the dishes the customer relish. The taste, smell, texture, ingredients, and dishes evoke not just the memories of food and people from the past of these characters but also the place and the setting (where the character belongs to). Each episode introduces a new character with a new story and the past that they deal with while the food is prepared and consumed. The stories about people in this show and around the world might be based on individual experiences but the emotions are both individual and universal at the same time.